Stories of art - Elkins, James 1955- (Routledge, Taylor & Francis Group, 2025)
"A thoughtful, engaging and intimate history of art that offers a critical analysis of the assumptions on which the entire discipline of art history depends. Concise and original, this accessible second edition continues to act as an antidote to the behemoth art history textbooks of the past. Cultures have their own stories - about themselves, about other cultures - and to hear them all is one way to hear the multiple stories that art tells. James Elkins persuasively demonstrates there can never be one story of art now that art historians are concerned with gender, diversity, inclusiveness, and decolonization. Stories of Art is an interactive, iconoclastic text, encouraging readers to imagine how they would present art history in an age of multiple narratives. Elkins discusses decolonizing the discipline, representing race and ethnicity, Eurocentrism, postnationalism, and indigenous voices while examining histories of art written in China, Persia, Turkey, and India. This new edition features QR codes to 27 short videos that introduce challenging ideas about art and history in a clear and open way, encouraging active reading, and including ideas for writing exercises and class conversations. A must read for students and scholars interested in exploring the cultural function of art history"
Keywords: Art / Historiography / Methodology; Art criticism / Historiography / Methodology; Art / Historiography / Forecasting; Illustrated works